Emerging Challenges in Implementing Universal Health Coverage in Asia - Bredenkamp, Caryn; Evans, Timothy; Lagrada, Leizel; Langenbrunner, John C.; Nachuk, Stefan; Palu, Toomas (Elsevier, 2015)
As countries in Asia converge on the goal of universal health coverage (UHC), some common challenges are emerging. One is how to ensure coverage of the informal sector so as to make UHC truly universal; a second is how to design a benefit package that is responsive and appropriate to current health challenges, yet fiscally sustainable; and a third is how to ensure “supply-side readiness”, i.e. the availability and quality of services, which is a necessary condition for translating coverage into improvements in health outcomes. Using examples from the Asia region, this paper discusses these three challenges and how they are being addressed.